THE QUANTITY THEORY OF MONEY AND ITS LONG-RUN IMPLICATIONS: EMPIRICAL EVIDENCE FROM NIGERIA - Santos R. Alimi (European Scientific Journal, ESJ, 2012)
The Quantity Theory of Money (QTM) is one of the popular classical macroeconomic models that explain the relationship between the quantity of money in an economy and the level of prices of goods and services. This study investigates this relationship for Nigeria economy over the period of 1960 to 2009. To check the stationarity properties, we employed Augmented Dickey Fuller (ADF) and Phillips-Perron (PP) test and found all the concerned variables are stationary only in the first differenced form. Using Johansen cointegration method, the empirical findings indicate that there exists long run cointegrating relationship among the concerned variables. Then applying the Granger causality test, we found a unidirectional causal relationship running from money supply to inflation which provides evidence in support for monetarist.s view. In addition, this study does not provide evidence in supporting the well known fisher effect for Nigeria. Causality does not strictly run from inflation to interest rates as suggested by the Fisher hypothesis, instead a reversed causality between the variables is found. We finally used Wald test to verify the restrictions imposed on money aggregates and output, and we concluded and confirmed the proposition of quantity theory of money that inflation is a monetary phenomenon.